Removal, transport, and transformation of organic micropollutants in managed aquifer recharge: Insights from target and non-target analyses - Alessia Ore; Gabriel Sigmund; Jan Specker; Rick Helmus; Patricia Aguilar-Alarcón; Merijn Schriks; Annemarie P. van Wezel; Nora B. Sutton (Water Research, 2025)

A framework for evaluating less-than-lifetime exposures: advancing toxicological risk assessment for drinking water quality - Sanah Majid; Astrid Reus; Renske Hoondert; Mirjam Blokker; Amitosh Dash; Corine Houtman; Merijn Schriks; Milou M. L. Dingemans (Archives of Toxicology, 2025)
The increasing production and use of chemicals leads to a higher number of contaminants in (drinking) water sources, which poses significant challenges to those responsible for water quality. An important task for water companies and regulators is to ensure that (drinking) water quality does not compromise public health and confidence in water safety. A key component of this effort is toxicological risk assessment, which evaluates the safety of chemicals that may be present in water systems. Although there has been considerable progress in risk assessment methods, there is currently a lack of a clear approach to the risk assessment of chemicals in (drinking) water for which concentrations vary over time. In the current study, methods for the assessment of less than lifetime exposure (LTL) are presented that are particularly applicable for substances with time-varying concentrations in (drinking) water. The presented framework is a decision tree that helps experts to decide whether a measured or predicted LTL exposure to a chemical can lead to adverse health effects. To develop these methods, we used existing knowledge and incorporated new developments in toxicological risk assessment. A case study illustrates the application of the proposed approaches in a realistic scenario. The method can be used by risk assessors as a tool to improve the understanding of human exposure to contaminants in (drinking) water and to inform risk-based monitoring. In addition, it enables customised investigations and responses that lead to a more nuanced view of water quality and its impact on public health.

Forever legacies? Profiling historical PFAS contamination and current influence on groundwater used for drinking water - Mohammad Sadia; Marlene Kunz; Thomas ter Laak; Martin De Jonge; Merijn Schriks; Annemarie P. van Wezel (Science of The Total Environment, 2023)